The effectiveness of advanced cardiac testing on identifying risk for sudden cardiac arrest/death in athletes following COVID-19 infection during preparticipation examination: A critically appraised topic - Wysmierski, S.; Hall, E. A.; Garofalo, G.; Lopez, R. (International Journal of Athletic Therapy & Training, 2023)
Clinical Scenario: Due to the potential side effects in athletes, there is a need to evaluate for cardiac-related side effects due to COVID-19 infection during preparticipation examinations. Clinical Question: Does advanced cardiac testing during preparticipation examinations in athletes who have contracted the COVID-19 virus identify cardiac abnormalities? Summary of Key Findings: The literature was searched based on athletes` post-COVID-19 infection who were tested for risk of sudden cardiac arrest/death. The initial search yielded 32 studies, but 7 were excluded based on abstract content. Of the remaining 25 studies, 17 were excluded based on patient age or non-athletic populations. Four relevant studies met the inclusion criteria and were included. The need for cardiac screening and advanced cardiac testing was supported to identify risk of sudden cardiac arrest/death during preparticipation examinations in COVID-19-positive patients. Clinical Bottom Line: The use of advanced cardiac testing along with a comprehensive symptom and history questionnaire is essential to reduce cardiac complications due to COVID-19. Symptom-based questionnaires following COVID-19 infection can detect possible COVID-19-related cardiac abnormalities better than the standard cardiac symptom-based questionnaires alone. These combined screening measures for patients with a COVID-19 infection can safely help return athletes to sports. Strength of Recommendation: This recommendation has a strength of B based on Oxford Centre for Evidence-Based Medicine due to consistently lower quality limited evidence that supports the use of advanced cardiac testing in identifying heart-related complications and risk of sudden cardiac arrest/death in COVID-19-positive patients.